Switchable Redox Chemistry of the Hexameric Tyrosine-Coordinated Heme Protein - Kielb, Patrycja; Utesch, Tillmann; Kozuch, Jacek; Jeoung, Jae-Hun; Dobbek, Holger; Mroginski, Maria Andrea; Hildebrandt, Peter; Weidinger, Inez M. (Journal of Physical Chemistry B, 2017)
Hexameric tyrosine-coordinated heme protein HTHP from Silicibacter pomeroyi has been shown to exhibit peroxidase- and catalase-like activity. In the present study, detailed spectroscopic and electrochemical investigations were performed to analyze the redox properties and active site structure of HTHP. Potentiometric titration of HTHP in solution revealed a single redox transition at -0.54 V (vs Ag/AgCl), indicating six structurally identical tyrosine coordinates hemes. Cyclic voltammetry (CV) of immobilized HTHP afforded a distinctly more positive redox potential (-0.17 V) but failed to detect a transition at -0.54 V. Conversely, surface enhanced RR (SERR) spectroscopy provided evidence for both high- and low-potential transitions and for a partial loss of heme in the reduced state. The high-potential CV-active redox transition is attributed to the hemes of the barrel-shaped HTHP in a wheel-like orientation on the surface. Supported by coarse-grained simulations and SERR spectroscopy, the majority of HTHP is concluded to adopt a reverse-disc orientation, accounting for the low-potential transition. In view of the striking similarity of HTHP to the heme carriers HasA or HmbR regarding redox potential, Fe-Tyr ligation, and heme release, we propose heme transport as an alternative or additional function.
CRIS-Team Scopus Importer:2022-04-14